Depressive symptoms and its associated factor among elderly living in Kirtipur Municipality of Kathmandu valley, Nepal during covid-19 pandemic. - Sah, Sushma (2021)
SUMMARY: Geriatric Depression is an important public health problem in older adults and a leading cause of disability worldwide. It is often under-diagnosed and under-treated and is frequently associated with other co-morbid conditions, such as physical disability, anxiety as well as other general medical conditions Older persons may also face age discrimination in decisions on medical care, triage. The spread of COVID-19 in care homes and institutions is taking a devastating toll on older people's lives, with distressing reports indicating instances of neglect or mistreatment. Older persons who are quarantined or locked down with family members or caregivers may also face higher risks of violence, abuse, and neglect. Thus the main objective of this study is to find out the prevalence and associated factors of depressive symptoms among elderly living in Kirtipur municipality of Kathmandu district. The study design was descriptive cross-sectional study which followed a quantitative method Study population were elderly persons of age 60 years and above at the selected ward representative of the Kirtipur Municipality of the Kathmandu Valley. As per the sampling interval the samples were selected by maintaining interval of at least 2 household from previous sample to the next sample of household of the elderly population. In this way, Systematic Random Sampling (SRM) technique was applied to select the required study unit Face to face interview was done with the each participant to collect data from representative sample Structured questionnaire was used to measure independent variables. The validated tools of the Geriatric Depression Scale (GDS-15) was used to find out depressive symptoms (16). Coding was done to simplify data entry. Data entry was done by using EpiData 3.1 and analysis was done in SPSS v 20. The questionnaire were checked at the time of data collection for completeness of data. Data were expressed in the form of frequency, percentage and mean. The association between depressive symptoms and different variables were tested through chi-square test. The overall prevalence of depressive symptoms among elderly living in Kirtipur municipality of the Kathmandu district was 64.4.% (At 95% confidence interval: 52.365.6 )The level of depressive symptoms was measured by using the Geriatric Depression Scale (GDS-15). The prevalence of mild depressive symptoms was 18%, moderate depressive symptoms was 27.3 %, and severe depressive symptoms was 19.1%. While 35.5% of total sample were found to have minimal disturbance or normal. In this study, depressive symptoms among elderly living in the municipality were found to be significantly associated with socio-demographic variables like age (p<0.001), sex (p<0.001) ,ethnicity (p=0.013), education status (p<0.001 ),marital status (p<0.001),past family type (p<0.001) and health status variable like chronic physical health problem (p=0.002) ,individual factor of feeling of loneliness (p=0.009) along with social factor being victim to the stigma related to COVID-19(p=0.001 ) and being victim to physical or verbal abuse (p<0.001) while religion and present source of income were not found to be statistically significant with depressive symptoms. This study highlighted the high prevalence of depression in older persons. This is a serious unmet need with considerable public health and wider social ramifications. Much more can and needs to be done to improve the mental health of older persons in Nepal